SCD1 activation impedes foam cell formation by inducing lipophagy in oxLDL‐treated human vascular smooth muscle cells. Issue 8 (22nd May 2019) - Pi, Huifeng; Wang, Zhen; Liu, Mengyu; Deng, Ping; Yu, Zhengping; Zhou, Zhou; Gao, Feng
Abstract: The formation of fat‐laden foam cells, which contributes to the fatty streaks in the plaques of atheromas, is an important process in atherosclerosis. Vascular smooth muscle cells (VSMCs) are a critical origin of foam cells. However, the mechanisms that underlie VSMC foam cell formation are not yet completely understood. Here, we demonstrated that oxidized low‐density lipoprotein (oxLDL) inhibited lipophagy by suppressing lipid droplet (LD)‐lysosome fusion and increased VSMC foam cell formation. Moreover, although oxLDL treatment inhibited lysosomal biogenesis, it had no significant effect on lysosomal proteolysis and lysosomal pH. Notably, through TMT‐based quantitative proteomic analysis and database searching, 94 differentially expressed proteins were identified, of which 54 were increased and 40 were decreased in the oxLDL group compared with those in the control group. Subsequently, SCD1, a protein of interest, was further investigated. SCD1 levels in the VSMCs were down‐regulated by exposure to oxLDL in a time‐dependent manner and the interaction between SCD1 and LDs was also disrupted by oxLDL. Importantly, SCD1 overexpression enhanced LD‐lysosome fusion, increased lysosomal biogenesis and inhibited VSMC foam cell formation by activating TFEB nuclear translocation and its reporter activity. Modulation of the SCD1/TFEB‐mediated lipophagy machinery may offer novel therapeutic approaches for the treatment of atherosclerosis.